Differentiated Learning on the Topics of Temperature and Heat to Determine the Effect of the PBL Model on Student Learning Outcomes - Dunggio, Dian Pitaloka; Uloli, Ritin; Abdjul, Tirtawaty; Yusuf, Muhammad; Payu, Citron S.; Nurhayati, Nurhayati (Jurnal Pijar Mipa, 2025)
Differentiated learning is an attempt to adapt the learning process in the classroom to meet the individual learning needs of each student. This research aims to determine the effect of the Problem-Based Learning (PBL) model through a differentiated approach to temperature & heat topics on student learning outcomes. This research is experimental research, with the research design being One Group Pre-test and Post-test Design. The population of this study was class VII students of SMP Negeri 1 Tilongkabila. The sample consists of 3 classes, namely experimental class, replication 1, and replication 2 with the Cluster Random Sampling technique. The instruments used in this research are learning style tests, teaching modules, student worksheets, teaching topics, and written tests (pre-test and post-test) to see student learning outcomes. Then, the data is analyzed using descriptive and inferential statistics, including normality tests, hypothesis tests, and n-gain analysis. The average score for class VII students is greater than the criteria for achieving learning goals, shown by the average score of the experimental class of 83.92, replication 1 at 83.67, and replication 2 at 82.92, compared to the criteria for achieving learning goals of 70. Based on the hypothesis testing criteria for the class, experimental t-count 14.009 is more significant than t-table 2.035, replication 1 t-count 11.417 is more excellent than t-table 2.035, and replication 2 t-count 12.084 is more remarkable than t-table 2.035, so it can be said t-count is more prominent than t-table. Thus, the PBL model, through a differentiated approach, affects student learning outcomes.